2002
DOI: 10.2337/diabetes.51.4.1166
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Sarcoplasmic Reticulum Ca2+-ATPase Improves Myocardial Contractility in Diabetic Cardiomyopathy

Abstract: Diabetic cardiomyopathy is characterized by reduced cardiac contractility due to direct changes in heart muscle function independent of vascular disease. An important contributor to contractile dysfunction in the diabetic state is an impaired sarcoplasmic reticulum (SR) function, leading to disturbed intracellular calcium handling. We investigated whether overexpression of the SR calcium pump (SERCA2a) in transgenic mice could reduce the impact of diabetes on the development of cardiomyopathy. Diabetes was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
181
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(205 citation statements)
references
References 39 publications
15
181
0
4
Order By: Relevance
“…These responses appear to be present during the early stages of diabetic cardiac dysfunction and occur before signs of cardiac hypertrophy, LV dilation and fibrosis and systolic impairment as have been reported previously (3,4,29). Initiation of T 3 treatment during this early period of dysfunction preserves cardiac function and prevents the loss of the arteriolar resistance vessel network.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…These responses appear to be present during the early stages of diabetic cardiac dysfunction and occur before signs of cardiac hypertrophy, LV dilation and fibrosis and systolic impairment as have been reported previously (3,4,29). Initiation of T 3 treatment during this early period of dysfunction preserves cardiac function and prevents the loss of the arteriolar resistance vessel network.…”
Section: Discussionsupporting
confidence: 64%
“…DM and hypothyroidism produce similar negative effects on cardiac function and are associated with impaired contractility (3,7,8,23), α to β myosin heavy chain (MHC) isoform shift (7,8,13,24), microvessel/blood flow abnormalities (4,13,(25)(26)(27), and dysregulation of Ca 2+ handling (23,(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpression of SERCA2 by transgenesis was protective against diabetic cardiomyopathy as well as cardiac dysfunction induced by chronic pressure overload. 55,56 Similarly, del Monte et al 57,58 showed that increased SERCA2 protein expression, or expression of an antisense phospholamban RNA, each improved contractile function of failing human ventricular myocytes in vitro. Moreover, adenovirus-mediated overexpression of SERCA2 in a pressure-overload rat model of heart failure produced a rescue in depressed cardiac function, myocardial energetics, and survival.…”
Section: Manipulation Of Serca2-phospholamban Alters Heart Failure Inmentioning
confidence: 97%
“…Several mechanisms are suggested for the pathogenesis of glucose-triggered cardiac dysfunction including prolonged action potential, impaired excitation-contraction coupling, loss of myofilament Ca 2+ sensitivity, elevated oxidative stress, intracellular Ca 2+ dysregulation and dampened insulin-like growth factor I (IGF-1) signaling (Cai & Kang 2001, Esberg & Ren 2003, Lagadic-Gossmann et al 1996, Ren 2000. Most of these speculations have received convincing support from clinical and experimental studies using antioxidant, gene delivery and IGF-1 as therapeutic remedies for cardiovascular complications in diabetes (Goo et al 1996, Ren et al 1999a, Trost et al 2002, Norby et al 2002. Nevertheless, the precise cellular signaling mechanism behind glucose toxicity-induced cardiac mechanical dysfunction and the therapeutic value of IGF-1 against hyperglycemia remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%